Autonomic testing in healthy subjects – preliminary observations - Chelimsky, Gisela (Clin Auton Res, 2012)
Autonomic testing is used clinically. Yet, the prevalence of “abnormal” variants in the healthy population have not been reported. We report the results of autonomic testing in healthy females > 18 years, in whom we found decrease or absent sudomotor function in 1–2 locations. These findings should caution physicians in the interpretation of autonomic testing. This report underscores the need of larger studies to determine the prevalence of these findings